Quality Improvement of Polycarbonate Medical Device by Moldex3D and Taguchi DOE - Upoma Saha; Wael Mokhtar (Journal of Manufacturing and Materials Processing)
Incorporating a new design combined with a thermoplastic material without having a prior process database may cause numerous defects in the molded part. Along with the initial setup cost, the scrape due to defects can add additional costs to the production. To address such issues, the numerical analysis tool Moldex3D was used to conduct simulations, and Taguchi Design of Experiment (DOE) was performed to optimize the process parameters. For this study, a classic medical device like the safety goggle model has been chosen as a subject. An amorphous material, polycarbonate, was used because of its transparent and significant thermal properties. The most influential defects, like the warpage and short shot, needed to be addressed together. Process parameters like melt temperature, injection speed, coolant temperature, and packing pressure were considered to address those defects. The goal of this work was to improve both warpage and short-shot defects at the same time using the same combination of process parameters. By performing the simulation and statistical analysis method, 25% of warpage defects had been reduced in the molded part. A total of 2.3% of any potential short-shot defect reduction was recorded. Additionally, 300 °C melt temperature, 80 mm/s injection speed, 10 MPa packing pressure, and 100 °C coolant temperature were the best combinations for the part that had uneven thickness and narrow flow channels. The combinations to reduce potential short shots were 280 °C melt temperature, 40 mm/s injection speed, 10 MPa packing pressure, and 90 °C coolant temperature. Moreover, packing pressure for the warpage and melt temperature for the short shots were the most significant factors of all.